Phytochemicals Derived from Agricultural Residues and Their Valuable Properties and Applications - Marta Oleszek; Iwona Kowalska; Terenzio Bertuzzi; Wiesław Oleszek (Molecules, 2023)
Billions of tons of agro-industrial residues are produced worldwide. This is associated with the risk of pollution as well as management and economic problems. Simultaneously, non-edible portions of many crops are rich in bioactive compounds with valuable properties. For this reason, developing various methods for utilizing agro-industrial residues as a source of high-value by-products is very important. The main objective of the paper is a review of the newest studies on biologically active compounds included in non-edible parts of crops with the highest amount of waste generated annually in the world. The review also provides the newest data on the chemical and biological properties, as well as the potential application of phytochemicals from such waste. The review shows that, in 2020, there were above 6 billion tonnes of residues only from the most popular crops. The greatest amount is generated during sugar, oil, and flour production. All described residues contain valuable phytochemicals that exhibit antioxidant, antimicrobial and very often anti-cancer activity. Many studies show interesting applications, mainly in pharmaceuticals and food production, but also in agriculture and wastewater remediation, as well as metal and steel industries.